Strategies to Survive MSMEs (Small and Medium-Sized Micro Enterprises) in Kendari City During the Covid-19 Pandemic (Case Study in Kambu Subdistrict) - Nila Yarni Sari; Lukman Yunus; Munirwan Zani (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
Micro, small and medium enterprises (MSMEs) are one of the business fields that have an essential role in economic growth in Indonesia. The part of micro, small and medium enterprises (MSMEs) is also often associated with the government's efforts to reduce poverty and equalize income. Still, the resilience of micro, small and medium enterprises (MSMEs) in Indonesia is being tested again in the face of economic impacts due to the spread of the COVID-19 virus. This study aims to determine the effect of the COVID-19 pandemic on MSMEs in the Kambu District and find out the strengths, weaknesses, opportunities, and threats to micro, small and medium enterprises in Kambu District and strategies for SMEs to be able to maintain their business during the COVID-19 pandemic. The research was conducted from October-September 2021 in Kambu District. The population in this study is micro, small and medium enterprises (MSMEs) in Kambu District, totalling 81 units who are engaged in the culinary business, using the cluster random sampling technique method, which is a random sampling that is not individual, but small unit groups, which takes 20% of the entire population to make a sample so that 16 people are obtained as research samples. Data analysis used SWOT analysis using IFAS (Internal Factor Analysis Strategic) and EFAS (External Factor Analysis Strategy) matrices.